2021
DOI: 10.1097/inf.0000000000003198
|View full text |Cite
|
Sign up to set email alerts
|

Performance of RT-PCR on Saliva Specimens Compared With Nasopharyngeal Swabs for the Detection of SARS-CoV-2 in Children

Abstract: Background: Saliva reverse transcriptase-Polymerase chain reaction (RT-PCR) is an attractive alternative for the detection of severe acute respiratory syndrome coronavirus 2 in adults with less known in children. Methods: Children with coronavirus disease 2019 symptoms were prospectively enrolled in a 1-month comparative clinical trial of saliva and nasopharyngeal (NP) RT-PCR. Detection rates and sensitivities of saliva and NP RT-PCR were compared as well as discordant NP and saliva RT-PCR findings including v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 23 publications
4
17
0
Order By: Relevance
“…To our knowledge, this study is the largest paediatric study comparing OSS with the established gold standard. The results are in concordance with the few studies performed on children 5 7 9 10 24. A recent study performed in Dubai with 476 children demonstrated a sensitivity even higher (87.7%) than found here; however, the authors used a saliva sample rather than saliva swabs, and the children were older (mean 10.8 years old) 10.…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, this study is the largest paediatric study comparing OSS with the established gold standard. The results are in concordance with the few studies performed on children 5 7 9 10 24. A recent study performed in Dubai with 476 children demonstrated a sensitivity even higher (87.7%) than found here; however, the authors used a saliva sample rather than saliva swabs, and the children were older (mean 10.8 years old) 10.…”
Section: Discussionsupporting
confidence: 91%
“…To allow for larger sample sizes without additional medical staff, in an accompanying sub-study, we evaluated the Salivette ® saliva collection system for children aged 3 to 11 [ 17 ]. Accordingly, saliva has been shown to be a well-established diagnostic specimen for detecting SARS-CoV-2 RNA [ 18 , 19 , 20 , 21 , 22 ], a child-friendly sampling alternative to swab-based methods [ 23 , 24 ] and one potentially suitable for the mass screening of children [ 25 ]. The findings in our evaluation of the Salivette ® system confirmed that assessment [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only very few reports have addressed saliva sampling in pediatric cohorts [16]. Of note, two studies comparing naso-/oropharyngeal swabs and saliva samples in symptomatic children found an overall saliva sensitivity of 85.2% (up to 95.2% in patients with high viral load (≥10 4 copies/mL) in nasopharyngal swabs) and 87.7%, respectively [17,18]. The Salivette ® system has been proposed as a device for collecting saliva for SARS-CoV-2 testing in adults [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%